Menakar Kebijakan Pendidikan Nasional Dan Pendidikan Islam Di Indonesia Era Reformasi (Presiden Habibie Sampai Presiden Jokowi Jilid I) - Permana Octofrezi (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2020)
This article aims to describe the National Education and Islamic Education Policy established by the government from the time of President Habibie in 1998 to President Jokowi in 2014 in the reform era. In detail, this text wants to reveal several things, namely: First, the meaning of reform; Second, what are the forms of national education policies and Islamic education in the reform era during the era of President Habibie, President Abdurrahman Wahid, President Megawati, President Susilo Bambang Yudhoyono to President Joko Widodo Volume I. This research method uses literature study or literacy. The results of this literature study show broadly that; During the Habibie era, the most striking policy was educational autonomy, where there was decentralization. Some education policies have begun to be handled by the regions, such as teacher regulation, teacher payroll, some local content curricula, all handled by the regions. After that, during the time of President Megawati, Islamic Religious Education became a compulsory subject in public universities, due to the new National Education System in 2003. During the time of President Susilo Bambang Yudhoyono, the welfare of teachers and lecturers began to be taken into account by providing certification and other honorary benefits, in addition to optimizing the 20 percent budget for education. Meanwhile, during President Jokowi's Volume I, a striking policy was the development of the latest curriculum, namely the 2013 Curriculum (K-13).